Misi Dakwah Profetik Dalam Pendidikan Islam Di Era Milenial - Taufiq Taufiq; Nur Allan Lasido (Ahsan: Jurnal Dakwah dan Komunikasi, 2022)
This article aims to outline how prophetic proselytizing missions in Islamic education in the millennial era. Several circles have long discussed the mission of prophetic proselytizing. Referring to the activity of inviting and calling for goodness must be based on these three pillars, namely the value of transcendence which is the orientation and vision of a da'i's life, always to improve the relationship of the dignity of fellow human beings, and the liberation to rid oneself of dirt, weakness, deprivation, and backwardness. Any weakness that drives Islam's mission to misguidance must be immediately liberated through prophetic proselytizing. Using qualitative descriptive research methods. The design of this research was chosen through research processed from the phenomenon of Islamic Education in the face of changing conditions adapted to the principles of the prophetic proselytizing mission. In obtaining data, the author tries to collect a series of data from related theories and the latest Islamic Education phenomena. The results of this study explained that prophetic proselytizing based on three keywords, namely Humanization, Liberation, and Transcendence, became a movement from the superstructure to infrastructure. This movement is part of a special total consciousness in the proselytizing movement. Part of the main consciousness needed is abstract philosophical consciousness meaning theological consciousness leads to strategic and tactical awareness. Keywords: Prophetic Da'wah, Islamic Education, Millennial Era